LFRSNet: A robust light field semantic segmentation network combining contextual and geometric features - Yang, Da; Zhu, Tongyu; Wang, Shuai; Wang, Sizhe; Xiong, Zhang (Frontiers in Environmental Science, 2022)
Light field (LF) semantic segmentation is a newly arisen technology and is widely used in many smart city applications such as remote sensing, virtual reality and 3D photogrammetry. Compared with RGB images, LF images contain multi-layer contextual information and rich geometric information of real-world scenes, which are challenging to be fully exploited because of the complex and highly inter-twined structure of LF. In this paper, LF Contextual Feature (LFCF) and LF Geometric Feature (LFGF) are proposed respectively for occluded area perception and segmentation edge refinement. With exploitation of all the views in LF, LFCF provides glimpse of some occluded areas from other angular positions besides the superficial color information of the target view. The multi-layer information of the occluded area enhances the classification of partly occluded objects. Whereas LFGF is extracted from Ray Epipolar-Plane Images (RayEPIs) in eight directions for geometric information embedding. The solid geometric information refines object edges, especially for occlusion boundaries with similar colors. At last, Light Field Robust Segmentation Network (LFRSNet) is designed to integrate LFCF and LFGF. Multi-layer contextual information and geometric information are effectively incorporated through LFRSNet, which brings significant improvement for segmentation of the occluded objects and the object edges. Experimental results on both realworld and synthetic datasets proves the state-of-the-art performance of our method. Compared with other methods, LFRSNet produces more accurate segmentation under occlusion, especially in the edge regions.